Approximate solutions of the Schrödinger equation with energy-dependent screened Coulomb potential in D – dimensions - Okorie, Uduakobong Sunday; Ikot, Akpan Ndem; Amadi, Precious Ogbonda; Ngiangia, Alalibo Thompson; Ibekwe, Etebong Emmanuel (Eclética Química, 2020)
Within the framework of the conventional Nikiforov-Uvarov method and a new form of Greene-Aldrich approximation scheme, we solved the Schrödinger equation with the energy-dependent screened Coulomb potential. Energy eigenvalues and energy eigenfunctions were obtained both approximately and numerically at different dimensions. The energy variations with different potential parameters, quantum numbers and energy slope parameter, respectively were also discussed graphically. The major finding of this research is the effect of the energy slope parameter on the energy spectra, which is seen in the existence of two simultaneous energy values for a particular quantum state. Our special cases also agree with the results obtained from literature, when the energy slope parameter is zero.